2016
DOI: 10.1002/ecs2.1314
|View full text |Cite
|
Sign up to set email alerts
|

Release date influences first‐year site fidelity and survival in captive‐bred Vancouver Island marmots

Abstract: Maximizing survival in reintroduced, captive‐bred animals requires evaluation to identify best practices. This is particularly true for critically endangered species like the Vancouver Island marmot, endemic to British Columbia, Canada. From 2003 to 2010, 301 captive‐bred marmots were implanted with transmitters and released at extinct colony locations and other potentially preferred sites to bolster wild populations and establish new colonies. We evaluated release success based on three criteria: (1) site fid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 69 publications
1
23
0
Order By: Relevance
“…Consistent with release strategy studies comparing captive-bred with wild-born individuals (Letty et al, 2007), translocations of wild-born marmots from Mt Washington yielded the highest post-release survival rates. Sex and age effects on postrelease survival of marmots were consistent with Jackson et al (2016a), with greater survival for two-year-old marmots compared to other age classes, and females compared to males. Our analysis suggests that captive-bred marmots take 2 years to overcome release effects in Strathcona and reach annual survival probabilities comparable to those of wild-wild individuals.…”
Section: Discussionsupporting
confidence: 60%
See 4 more Smart Citations
“…Consistent with release strategy studies comparing captive-bred with wild-born individuals (Letty et al, 2007), translocations of wild-born marmots from Mt Washington yielded the highest post-release survival rates. Sex and age effects on postrelease survival of marmots were consistent with Jackson et al (2016a), with greater survival for two-year-old marmots compared to other age classes, and females compared to males. Our analysis suggests that captive-bred marmots take 2 years to overcome release effects in Strathcona and reach annual survival probabilities comparable to those of wild-wild individuals.…”
Section: Discussionsupporting
confidence: 60%
“…For captive-wild marmots released at any age, Jackson et al (2016a) found 67% of newly released marmots hibernated within one km of their release site. Marmots released in July, like most marmots in this study, were less likely to be site-faithful than marmots released later in the summer, but earlier release dates were preferred because of improved overwinter survival (Jackson et al, 2016a). While we could not differentiate between mortality and permanent emigration from the study area, it is likely that most dispersing individuals do not locate a colony and are effectively lost to the population.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations